Reusable fiberglass and polyester combined total contact cast system for treatment of plantar diabetic foot ulcers: efficacy and cost-effectiveness - Erkin, Alper; Açıl, Hande Cengiz; Yılmaz, Ayşe Çelik; Demirci, Taner; Eberleın, Thomas (Frontiers in Endocrinology, 2025)
BackgroundThe basic principles of TCC are to achieve complete contact of the cast with the entire plantar surface of the foot and distribute the pressure at the sole. This method also reduces the shear forces generated at the wound edges and increases the healing potential of the wound.PurposeThis study aimed to evaluate the effectiveness of a reusable fiberglass and polyester combined total contact cast (TCC) system in the treatment of plantar diabetic foot ulcers.Study DesignA retrospective review was conducted on 70 patients treated with the reusable TCC system between January 2020 and September 2022.MethodsThe hospital’s electronic medical record system was searched for cases using CPT code 29445 (application of a rigid total contact cast, half leg, adult). Patients included had persistent plantar ulcers at pressure points unresponsive to standard care and were treated with the TCC system until granulation tissue developed. Cases involving deep tissue infections or osteomyelitis were managed according to international diabetic foot guidelines.ResultsOut of 70 patients, 53 (75.7%) achieved complete wound closure. Seventeen patients showed no healing; among these, 9 underwent minor amputations and 1 required a major amputation. No significant difference in healing time was found based on ulcer location (forefoot, midfoot, hindfoot) (p=0.503).ConclusionThe reusable fiberglass and polyester TCC system is a practical and cost-effective option for diabetic foot ulcers, offering outcomes similar to traditional TCCs. Continued use is recommended, with future research focusing on improving patient adherence and optimizing comfort in hybrid designs.